Analisis dan Perbaikan Sistem Kompensasi pada UKM Kakaku Coffee dengan Metode Adhered (Berhimpit) dan Overlapping (Tumpang Tindih) - Alfito, Fiqih; Dalhats, Akbelhaqqi; Saputra, Mochammad Giffari; Priditya, Nazwa; Christin, Stefani; Kartika, Lindawati (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
According to Permenaker Nomor Tahun 2017, entrepreneurs who have not yet prepared a wage structure and scale are required to prepare and implement a wage structure and scale by adjusting the company's capabilities and paying attention to the applicable minimum wage. This research was conducted to analyze and provide recommendations for improving the compensation system at UKM Kaku Coffee in East Jakarta. This research is quantitative and qualitative research carried out by taking primary and secondary data on the SME Kakaku Coffee. Primary data in this research was obtained through in-depth interviews directly with managers and employees. Meanwhile, secondary data was obtained from literature related to the Compensation Management Course, research in the form of identity, certification, company data from direct meetings and electronic communication media (WhatsApp) as well as additional information from the internet. Data processing was carried out by taking 21 employees as survey respondents. Based on the results of the research, the recommendation for improving the compensation system at SME Kakaku Coffee is to create a wage structure and scale using the overlapping method. With this new compensation system, a salary increase of Rp. 3,259,400 or 6.50% was found, which is still within the range of salary expenditure by the owner of SME Kakaku Coffee